1991
DOI: 10.1007/bf00050794
|View full text |Cite
|
Sign up to set email alerts
|

Orthotopic implantation of human colon carcinomas into nude mice provides a valuable model for the biology and therapy of metastasis

Abstract: Human colon carcinomas (HCC) are heterogeneous for a variety of biological properties that include invasion and metastasis. The presence of a small subpopulation of cells with a highly metastatic phenotype has important clinical implications for diagnosis and therapy of cancer. For this reason, it is important to develop animal models for the selection and isolation of metastatic variants from human colon cancers and for testing the metastatic potential of these cells. We have implanted cells from more than 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
88
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(93 citation statements)
references
References 62 publications
5
88
0
Order By: Relevance
“…Scale bars=100um and its potential of metastasis. The findings of our study conform to the related reports of previous studies (Fidler 1991;Kuo et al, 1995). In the experiment we found the liver metastatic rate of the orthotopic model was even higher than that of clinical gallbladder carcinoma, which may be due to the cases that we chose.…”
Section: Discussionsupporting
confidence: 92%
“…Scale bars=100um and its potential of metastasis. The findings of our study conform to the related reports of previous studies (Fidler 1991;Kuo et al, 1995). In the experiment we found the liver metastatic rate of the orthotopic model was even higher than that of clinical gallbladder carcinoma, which may be due to the cases that we chose.…”
Section: Discussionsupporting
confidence: 92%
“…Although subcutaneous sites are easily accessible and allow rapid screening of new antitumour compounds, increasing evidence demonstrates that faithful reproduction of the tumour microenvironment and more predictive treatment responses occur with orthotopic tumour implantation, in which either tumour cells or tumour fragments (surgical orthotopic implantation) are implanted within the organ corresponding to the original human tumour site (Fidler, 1991;Hoffman, 1999;Killion, 1998).…”
Section: The Orthotopic Animal Modelmentioning
confidence: 99%
“…Orthotopic implantation allows rapid growth of local tumour and spreading of distant metastases and seems to recapitulate the morphology and the growth characteristics of clinical disease (Fidler, 1986;Fidler, 1991;Hoffman, 1999). Indeed, clinical observation have suggested that the organ environment can influence the response of tumour to chemotherapies (Fidler, 2002;Killion, 1998) and orthotopic models allow to obtain a vasculature network similar to that of patient being useful for antivascular drug discovery.…”
Section: The Orthotopic Animal Modelmentioning
confidence: 99%
“…This use is mainly due to ideal characteristics, which include rapid tumor growth, easy handling, and the ability to accept human cells. Athymic mice have been used as an important biomedical tool 1,2,[3][4][5][6][7][8][9][10] . Athymic mice accept xenogeneic and allogeneic grafts, including those of malignant tumors, because they are immunocompromised.…”
Section: Introductionmentioning
confidence: 99%
“…Realistic models of colorectal cancer are necessary to study cancer biology and evaluate therapeutic interventions. Currently, it is the most accurate orthotopic representation of human colon cancer is via a cecal injection 6,7,8,9 . However, real-time observation and repeated sampling of implanted tumor is difficult to achieve in those model.…”
Section: Introductionmentioning
confidence: 99%